KIC011764567: An evolved Kepler‐star showing substantial flare activity. Issue 1 (10th February 2017) - Kitze, M.; Akopian, A. A.; Hambaryan, V.; Torres, G.; Neuhäuser, R.
Abstract : We intensively studied the flare activity on the stellar object KIC011764567. The star was thought to be a solar type, with a temperature of T e f f ≈(5640±200) K, log( g ) = (4.3 ± 0.3) dex, and a rotational period of P rot ≈22 days. High‐resolution spectra turn the target to an evolved object with T eff =(5300±150) K, a metalicity of [m/H] =(−0.5±0.2), a surface gravity of log( g ) = (3.3 ± 0.4) dex, and a projected rotational velocity of v sin i = (22 ± 1) km s −1 . Within an observing time span of 4 years, we detected 150 flares in Kepler data in the energy range 10 36 –10 37 erg. From a dynamical Lomb–Scargle periodogram, we have evidence for differential rotation as well as for stellar spot evolution and migration. On analyzing the occurrence times of the flares, we found hints for a periodic flare frequency cycle of 430–460 days, a significant increase with an increase in threshold of the flares' equivalent duration. One explanation is a very short activity cycle of the star with that period. Another possibility, also proposed by others in similar cases, is that the larger flares may be triggered by external phenomena, such as magnetic interaction with an unseen companion. Our high‐resolution spectra show that KIC011764567 is not a short‐period binary star.